Significance of community in Malaysian Higher Educational Institutions sustainability - Saadatian, Omidreza; Salleh, Elias; Mohd Tahir, Osman; Dola, Kamariah (Universiti Putra Malaysia Press, 2011)
Since the beginning of environmental movement, academicians and policy makers have been focusing on the institutions of higher learning. The first document on campus sustainability, the Talloires Declaration, which was ratified by 413 universities, including University Malaya, addressed the concept of community aspect of Higher Educational Institutions (HEI) sustainability. This article is a position paper with the objective to highlight the importance of community in the sustainability of Malaysian Higher Learning Institutions (MHLE). In carrying out this study, the archival and document analysis method was employed, whereby different scholars’ articles, dissertations, and tools were reviewed. Further validation of the findings was accomplished by employing the questionnaire survey method. Various documents were analysed thoroughly to figure out how the issue of community and the effects on campus sustainability were addressed. Besides a literature review, observation and interview were also utilized to figure out the challenges faced by Malaysian Higher Educational Institutions. The results indicated that community and campus sustainability have a linear relationship. In the context of MHEI, ethnical polarization, poor command of English and imbalance distribution of gender are the challenges. Likewise, the community is one of the most important aspects and is given high priority. Thus, the findings of this study could serve as a reference for researchers, institutions, and universities that are working on topics related to sustainability in higher education